2012
DOI: 10.3389/fpsyt.2012.00056
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Electrophysiological Effects of Transcranial Direct Current Stimulation of the Parietal Cortex in a Visuo-Spatial Working Memory Task

Abstract: Impairments of working memory (WM) performance are frequent concomitant symptoms in several psychiatric and neurologic diseases. Despite the great advance in treating the reduced WM abilities in patients suffering from, e.g., Parkinson’s and Alzheimer’s disease by means of transcranial direct current stimulation (tDCS), the exact neurophysiological underpinning subserving these therapeutic tDCS-effects are still unknown. In the present study we investigated the impact of tDCS on performance in a visuo-spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 94 publications
5
36
3
Order By: Relevance
“…Although the parietal cortex has been implicated in numerical processing, it has been also associated with various attentional and executive control functions, which include components of spatial shifts of attention (e.g., Bolognini, Fregni, Casati, Olgiati, & Vallar, 2010;Bolognini, Olgiati, Rossetti, & Maravita, 2010), selection processes (e.g., Weiss & Lavidor, 2012), and working memory capacity (Heimrath, Sandmann, Becke, Müller, & Zaehle, 2012;Tseng et al, 2012). Although it is not likely that participants had relied on working memory in the task, in particular at longer sequence durations, at which working memory capacity would severely degrade performance (see Brezis et al, 2015, for a detailed study of this question), it could nonetheless be argued that the enhanced accuracy we observed under parietal stimulation is due solely to enhanced attentional capacities rather than to enhanced numerical precision.…”
Section: Discussionmentioning
confidence: 99%
“…Although the parietal cortex has been implicated in numerical processing, it has been also associated with various attentional and executive control functions, which include components of spatial shifts of attention (e.g., Bolognini, Fregni, Casati, Olgiati, & Vallar, 2010;Bolognini, Olgiati, Rossetti, & Maravita, 2010), selection processes (e.g., Weiss & Lavidor, 2012), and working memory capacity (Heimrath, Sandmann, Becke, Müller, & Zaehle, 2012;Tseng et al, 2012). Although it is not likely that participants had relied on working memory in the task, in particular at longer sequence durations, at which working memory capacity would severely degrade performance (see Brezis et al, 2015, for a detailed study of this question), it could nonetheless be argued that the enhanced accuracy we observed under parietal stimulation is due solely to enhanced attentional capacities rather than to enhanced numerical precision.…”
Section: Discussionmentioning
confidence: 99%
“…Many other groups have similarly reported changes in cortical synchrony across frequency bands following traditional tDCS using saline soaked sponge electrodes. In general these studies assessed electrophysiological activity using EEG before and after a period of stimulation of the region of interest [17], [39]–[42], or EEG recordings interleaved between short periods of stimulation [43], [44]. tDCS over the left motor cortex has previously been shown to induce changes in motor imagination ERD/ERS in a polarity dependent manner, although reports of the polarity specific effects vary [11], [45], [46].…”
Section: Discussionmentioning
confidence: 99%
“…EEG has been widely used to study the neural correlates in cognitive paradigms such as visual working memory (VWM) [12][18], and hence is now used to investigate the modulatory effects of tDCS. These studies suggest a strong direct effect of tDCS on EEG activity in healthy subjects, both at rest [19] and during cognitive tasks [20][24]. For example, Keeser et al [7] found increased amplitude of the P2 and P3 components in a working memory task localized to the parahippocampal gyrus.…”
Section: Introductionmentioning
confidence: 94%